Carbon footprint patterns of domestic migrants in China and 1.5 °C mitigation pathways - Rui Wang; Guangwu Chen; Yafei Wang; Jiahao Feng (Environmental Research Letters, 2022)
Rural–urban migration and the growing carbon footprints (CFs) will challenge the world in keeping the global average-temperature increment below 1.5 °C compared to preindustrial levels. We first quantified the CFs of migrant consumption in 30 Chinese provinces in 2013 and 2015. An integrated approach was developed to match the Chinese multiregional input–output table with household survey data covering 200 000 migrant survey samples. Furthermore, we adopted the three shared socioeconomic pathways (SSPs) to explore the carbon budgets and trajectories of the migrants and permanent residents to align with the 1.5 °C climate target. The results suggest that the average migrant CFs ranged from 2.3 to 2.6 tCO _2 e per capita in 2015. To align with 1.5 °C pathways, the emissions of migrants should be held below 3.4 tCO _2 e per capita under the 12 SSPs–1.9 scenarios from 2020 and keep decreasing to net-zero before 2050. To ensure citizenry progress in improving well-being without overshooting dual carbon targets, high-emitting migrants need to reduce their emissions substantially.